2022
DOI: 10.1590/1678-4685-gmb-2021-0153
|View full text |Cite
|
Sign up to set email alerts
|

Common BMI and diabetes-related genetic variants: A pilot study among indigenous people in the Brazilian Amazon

Abstract: This study was carried out to investigate the frequency of genetic variants related to body mass index (BMI) and type 2 diabetes (T2D) and evaluating the potential impact of risk alleles on susceptibility to these disorders in six indigenous peoples from Brazilian Amazon region. The majority of Fst values for pairwise population comparisons among the indigenous groups are low or moderate. The indigenous people show high values of differentiation with Africans, Europeans and Southeast Asians and moderate values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
2
0
2
Order By: Relevance
“…similar finding exists among Brazilian population [17]. changes from expected frequency could be due to cross-breeding that may have occurred in previous generations [18], considering the multi-ethnic nature of the geographical population of the study area this might apply to the genetic drift observed for the studied FTO variants.…”
Section: Hardy-weinberg Statistical Test Of Fto Gene Variantssupporting
confidence: 71%
See 1 more Smart Citation
“…similar finding exists among Brazilian population [17]. changes from expected frequency could be due to cross-breeding that may have occurred in previous generations [18], considering the multi-ethnic nature of the geographical population of the study area this might apply to the genetic drift observed for the studied FTO variants.…”
Section: Hardy-weinberg Statistical Test Of Fto Gene Variantssupporting
confidence: 71%
“…The FTO gene exists in different genetic forms known as variants of FTO polymorphisms. FTO gene rs9939609 SNP is significantly associated with obesity, With the AA genotype carriers having a 2.02 increased risk of developing obesity [5]. interdependece exist between biochemical parameters of T2D with FTO gene, namely insulin, glucose, HOMA, BMI, waist and hips circumference [6].…”
Section: Introductionmentioning
confidence: 99%
“…A desnutrição infantil é especialmente alarmante, com altas taxas de anemia por falta de ferro e atraso no crescimento e ganho de peso, frequentemente superando as médias regionais e nacionais. Ao mesmo tempo, a obesidade entre os adultos começa a se tornar um desafio sério em algumas comunidades indígenas (Leite et al, 2007;Capelli & Koifman, 2001;Vieira-Filho et al, 2004;Costa, 2007;Rodrigues et al, 2023;Diniz et al, 2022).…”
Section: Discussionunclassified
“…Entretanto, os perfis antropométricos apontam para condições Research, Society andDevelopment, v. 12, n. 7, e10012742557, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i7.42557 mais desfavoráveis durante os meses chuvosos, período em que as taxas de desnutrição em crianças aumentam e os adultos de ambos os sexos apresentam médias de peso corporal mais baixas (Leite et al, 2007). De maneira geral, Diniz et al (2022) verificou que a prevalência de excesso de peso em populações indígenas da Amazônia brasileira estudados foi menor do que a relatada para adultos urbanos brasileiros, assim como a prevalência de obesidade e obesidade central, com exceção dos Gavião Kyikatêjê e Asurini do Xingu, nos quais foram identificadas altas taxas de obesidade e obesidade abdominal. Esses resultados podem ser atribuídos às intensas mudanças culturais e ambientais que esses grupos têm vivenciado.…”
Section: Discussionunclassified
“…The misssense variant of rs4994 has been well studied and was first described as being associated with obesity in the Japanese population [60]. More recent studies have shown an association of this variant with obesity and T2DM in populations of East Asia [59], Iran [58], and the indigenous population of the Amazon [61]. The mechanism by which this variant acts is thought to be an alteration in receptor function leading to the decreased expression of hormone-sensitive lipase (HSL), most likely causing obesity [62].…”
Section: Variants In Adrb3mentioning
confidence: 99%